2018
DOI: 10.1111/nan.12479
|View full text |Cite
|
Sign up to set email alerts
|

The miR‐139‐5p regulates proliferation of supratentorial paediatric low‐grade gliomas by targeting the PI3K/AKT/mTORC1 signalling

Abstract: These findings provide the first evidence that down-regulation of miR-139-5p in supratentorial pLGG drives cell proliferation by derepressing PI3K/AKT signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 67 publications
(114 reference statements)
2
33
0
Order By: Relevance
“…Pharmacological inhibition of Vegfa was induced by treating SHH MB CSC cells for 72 h with 10, 20, 40 and 60 ng/ml anti-Vegf (MAB 293, R&D Systems). Synthetic miR-466f-3p (4464066, Thermo Fisher Scientific) or negative control (miRIDIAN CN-001000-01; Dharmacon) were used as previously described ( Catanzaro et al, 2018 ). Cell proliferation was evaluated by trypan blue exclusion assay ( Catanzaro et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological inhibition of Vegfa was induced by treating SHH MB CSC cells for 72 h with 10, 20, 40 and 60 ng/ml anti-Vegf (MAB 293, R&D Systems). Synthetic miR-466f-3p (4464066, Thermo Fisher Scientific) or negative control (miRIDIAN CN-001000-01; Dharmacon) were used as previously described ( Catanzaro et al, 2018 ). Cell proliferation was evaluated by trypan blue exclusion assay ( Catanzaro et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic miR-466f-3p (4464066, Thermo Fisher Scientific) or negative control (miRIDIAN CN-001000-01; Dharmacon) were used as previously described ( Catanzaro et al, 2018 ). Cell proliferation was evaluated by trypan blue exclusion assay ( Catanzaro et al, 2018 ). Oncosphere-forming assay of SHH MB CSC was performed as previously described ( Po et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are 18-25 nucleotide long non-coding RNAs that act as post-transcriptional regulators of gene expression. MiRNA "signatures/profiles" have been reported as specific in several cellular contexts and diseases (Catanzaro, et al, 2018;Catanzaro, et al, 2017;Esquela-Kerscher & Slack, 2006;Iorio & Croce, 2012;Miele, et al, 2013) as well as in response to therapy (Chan, Prado, & Weidhaas, 2011;Gasparri, et al, 2017;Gasparri, et al, 2018;Skinner, et al, 2014). Previous studies reported the aberrant expression of specific miRNAs in MTC tissues, suggesting these miRNAs as candidate biomarkers.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…For example, phosphatidylinositol 3-kinase (PI3K), a lipid kinase that regulates the levels of phosphorylated phosphatidylinositol at the plasma membrane and enhances glucose uptake and glycolysis in cancer cell metabolism, is targeted by miR-320, miR-123a, miR-422, miR-506, and miR-136 (127). Catanzaro et al showed evidence that downregulation of miR-139-5p in pediatric low-grade gliomas drives cell proliferation by regulating PI3K/AKT signaling (128). Furthermore, miR-33a/b, targets metabolic enzymes involved in fatty acid metabolism and the AMPK pathway, whereas miR-29b targets amino acid catabolism, which regulates cancer cell metabolism and biogenesis to support tumor growth and proliferation (61, 129-131).…”
Section: Mirnas Regulation Of Transcription Factors and Signaling Patmentioning
confidence: 99%